Sovereign Credit Ratings and Spreads in Emerging Markets : Does Investment Grade Matter? - Jaramillo, Laura (IMF Working Papers; Working Paper ;, 2011)
Sovereign investment grade status is often associated with lower spreads in international markets. Using a panel framework for 35 emerging markets between 1997 and 2010, thispaper finds that investment grade status reduces spreads by 36 percent, above and beyond what is implied by macroeconomic fundamentals. This compares to a 5-10 percent reduction in spreads following upgrades within the investment grade asset class, and no impact formovements within the speculative grade asset class, ceteris paribus. While global financial conditions play a central role in determining spreads, market sentiment improves with lower external public debt to GDP levels and higher domestic growth rates.